The anatomical variations of the additional communicating rami in the proximal sympathetic trunk: A human cadaveric study - Maxime Peetermans; Jens Vanlommel; Lawrence Van Look; Leen Uyttebroek; Paul Van Schil; Luc van Nassauw (Elsevier, 2023)
Background: In literature, four types of additional communicating branches of the sympathetic trunk are described. Data concerning location, presence, and variation of these rami are confusing and often incomplete. In this study, incidence of all additional rami of the upper thoracic sympathetic trunk at levels T2 to T5, including the nerve of Kuntz, were investigated, specifically examining a difference between right and left trunk and a possible intergender disparity. Material and methods: Microdissection of the proximal sympathetic chain was bilaterally performed in twenty fixed cadavers (ten male and ten female bodies). Gender, presence of the additional communicating rami and the nerve of Kuntz were obtained. Data were statistically analysed. Results: Every thoracic level had at least one normal ramus. Ascending rami were only observed at level T4 and T5. The lower thoracic levels had fewer descending rami. Intercostal rami were found at level T2 and T5. The mean incidence of the nerve of Kuntz was 0.65 rami per cadaver. This nerve was present bilaterally in 50% of dissected trunks. Conclusion: No statistically significant differences were found between the total amount of additional communicating rami and the nerve of Kuntz on the right compared to the left trunk, and no intergender difference was discovered. Peculiar, the nerve of Kuntz was present bilaterally in half of the dissected cadavers, with a mean incidence of 0.65 rami per cadaver. This study provides insight in the anatomical variation of the additional communicating rami of the proximal sympathetic chain and will have a benefit on thoracic sympathectomy.